E. Calderón Dorda, A. Morales Ortiz y M. Valverde Sánchez (eds.), Koinòs Lógos homenaje al profesor José García López, Murcia, Servicio de Publicaciones de la Universidad de Murcia, 2006, 1070 págs. ISBN: 84-8371-609-0 (Minerva, 2019)
Review: E. Calderón Dorda, A. Morales Ortiz y M. Valverde Sánchez (eds.), Koinòs Lógos homenaje al profesor José García López, Murcia, Servicio de Publicaciones de la Universidad de Murcia, 2006, 1070 págs. ISBN: 84-8371-609-0